2022
DOI: 10.3390/vaccines10060849
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Profile of the Post-COVID Condition in Adults in Catalonia—A Mixed Method Prospective Cohort and Nested Case–Control Study: Study Protocol

Abstract: The diagnosis of the post-COVID condition is usually achieved by excluding other diseases; however, cognitive changes are often found in the post-COVID disorder. Therefore, monitoring and treating the recovery from the post-COVID condition is necessary to establish biomarkers to guide the diagnosis of symptoms, including cognitive impairment. Our study employs a prospected cohort and nested case–control design with mixed methods, including statistical analyses, interviews, and focus groups. Our main aim is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…The final regression analysis model demonstrated that elevated levels of anxiety and depression, the existence of PTSD-like symptoms, and the presence of COVID-related stigma at T1 are indicative of the likelihood of experiencing PTSD-like symptoms in the subsequent 4-month follow-up assessment. Previous research also showed that COVID-19 exacerbates psychological conditions such as anxiety and depression (e.g., Dacosta-Aguayo et al, 2022), and those, in turn, increase the likelihood of developing PTSD and similar conditions. Furthermore, as a consequence of labeling and harmful stereotyping due to the novelty, uncertainty, and person-to-person transmission of the virus (i.e., stigma), one may experience mental health problems, including extreme stress (Kang et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…The final regression analysis model demonstrated that elevated levels of anxiety and depression, the existence of PTSD-like symptoms, and the presence of COVID-related stigma at T1 are indicative of the likelihood of experiencing PTSD-like symptoms in the subsequent 4-month follow-up assessment. Previous research also showed that COVID-19 exacerbates psychological conditions such as anxiety and depression (e.g., Dacosta-Aguayo et al, 2022), and those, in turn, increase the likelihood of developing PTSD and similar conditions. Furthermore, as a consequence of labeling and harmful stereotyping due to the novelty, uncertainty, and person-to-person transmission of the virus (i.e., stigma), one may experience mental health problems, including extreme stress (Kang et al, 2021).…”
Section: Discussionmentioning
confidence: 94%